A new method for the analysis of combined operation of electro-osmotic dewatering and mechanical expression - Jami, Mohammed Saedi; Iwata, Masashi (2010)
Electro-osmosis is especially effective in removing liquid from sludge of colloidal particles for which conventional mechanical dewatering is not very successful. This work presents results of experimental work carried out to study and analyze the combined operation of electro-osmotic dewatering (EOD) and mechanical expression (ME) by use of the Terzaghi-Voigt combined model for considering creep deformation of the material. The EOD-ME process combines the advantage of electro-osmosis and mechanical dewatering and consequently results in reduced void ratio compared to individual operation.